Profitabilitas, Kebijakan Dividen, Dan Growth Opportunity Menentukan Nilai Perusahaan - Mentari, Ni Made Indah; Pratiwi, Ida Ayu Putu Eka; Astiti, Ni Putu Yeni Astiti Yeni (Sains: Jurnal Manajemen dan Bisnis, 2024)
The purpose of publicly traded companies (companies listed on the Indonesia Stock Exchange) is to generate profit in order to enhance their firm value. This research aims to analyze the influence of profitability, dividend policy, and growth opportunity on firm value. The study was conducted on property and real estate companies listed on the Indonesia Stock Exchange for the period of 2020-2022, using purposive sampling method, with a selection of 10 sample companies. Data collection in this research employed a non-participant observation method. Data analysis techniques in this study utilized multiple linear regression analysis. The results of the analysis indicate that profitability and dividend policy have a positive impact on firm value, while growth opportunity has a negative impact on firm value.